When Goods Became Data: The Barcode as an Economic Infrastructure - Zebo Shomirova; Shohruh Qutliboyev Sherzod o‘g‘li (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract. The barcode is widely perceived as a retail convenience technology; however, its economic significance extends far beyond point-of-sale efficiency. This article examines the barcode as a foundational standard that transformed physical goods into machine-readable data, enabling real-time measurement, coordination, and optimization across supply chains. Using a mixed analytical approach that combines historical analysis, institutional review, and secondary data synthesis, the study investigates how barcode standardization reduced transaction costs, improved inventory accuracy, accelerated turnover rates, and facilitated the emergence of data-driven retail and logistics models. The findings suggest that barcode adoption functioned as an infrastructural innovation, reshaping market transparency and operational efficiency while enabling second-order effects such as just-in-time production, platform economies, and globalized distribution networks. The article contributes to the literature on economic standardization by framing the barcode not as a marginal technological tool, but as a critical mechanism through which modern capitalism became quantifiable, scalable, and digitally integrated.